Front Cover: Grain Boundaries Boost Oxygen Evolution Reaction in NiFe Electrocatalysts (Small Methods 2/2021). Issue 2 (12th February 2021) - Park, Hoon Kee; Ahn, Hehsang; Lee, Tae Hyung; Lee, Jae Yoon; Lee, Mi Gyoung; Lee, Sol A.; Yang, Jin Wook; Kim, Sang Jun; Ahn, Sang Hyun; Kim, Soo Young; Lee, Chul‐Ho; Park, Eun Soo; et al.
Abstract : In article number 2000755 by Chul‐Ho Lee, Eun Soo Park, and Ho Won Jang, in situ electrochemic al observations to reveal the strong dependence of oxygen evolution reaction on grain boundary density is reported for the first time. Thermodynamically favorable aspects of the grain boundary for oxygen evolution reaction (OER) compared to the grain interior is demonstrated by various analyses. Grain boundary can elevate OER performance probably by modifying the reaction kinetics of the rate‐determining step.